Antimicrobial resistance trend of Salmonella typhi and paratyphi from 2011-2013: A descriptive study from tertiary care hospital of Nepal - Adhikari, Arjab; Sapkota, Supriya; Bhattarai, Utsuk; Raghubanshi, Bijendra Raj (Journal of Kathmandu Medical College, 2017)
Background: Enteric fever is a major public health problem in Nepal. Trends of drug resistance help in choosing optimal empiric therapy. Objective: The objective of this study was to determine antibiotic resistance pattern of Salmonella enterica serotype typhi and Salmonella enterica serotype paratyphi isolated from blood cultures. Methodology: A descriptive study was conducted using hospital records at KIST Medical College and Teaching Hospital, Nepal. Isolates from blood cultures between January 2011 and December 2013 were included in this study. Susceptibility to various antimicrobials was determined using modified Kirby-Bauer disk diffusion method. A chi-square for trend analysis was done to evaluate change in susceptibility over three years. Results: Out of 216 isolates, 68.05% were Salmonella typhi and 31.48% were Salmonella paratyphi A. In Salmonella typhi, there was significant increase in cefotaxime resistance(X2 = 4.951, p < 0.05) and ciprofloxacin resistance (X2 = 17.506, p < 0.001) whereas there was significant decrease in ampicillin resistance (X2 = 4.830, p < 0.05). No resistance was seen against ceftriaxone in Salmonella typhi and Salmonella paratyphi A. Resistance to chloramphenicol and cotrimoxazole was low as well, in both isolates. None of the isolates tested were multidrug resistant. Conclusion: There is emergence of resistance to cefotaxime whereas resistance to ciprofloxacin has made its use as empiric therapy questionable. Full susceptibility of ceftriaxone makes it an excellent antibiotic for empiric therapy. Decrease in resistance to chloramphenicol, cotrimoxazole and ampicillin may again make these agents useful. Journal of Kathmandu Medical College Vol. 6, No. 1, 2017, page: 9-13